LINC00470 Stimulates Methylation of PTEN to Facilitate the Progression of Endometrial Cancer by Recruiting DNMT3a Through MYC - Yi, Tiezhong; Song, Yicun; Zuo, Lingling; Wang, Siyun; Miao, Jintian (Frontiers in Oncology, 2021)
Objectives: Increasing researches emphasize the importance of long non-coding RNAs (lncRNAs) in the development of endometrial cancer (EC). There is wide recognition that LINC00470 is a critical participant in the tumorigenesis of cancers such as gastric cancer and glioblastoma, but its possible effects on EC progression remain to be explored. Methods: We collected EC tissues and cells, where the expression of LINC00470 was determined, and followed by the Kaplan-Meier analysis of EC patient survival. We next examined the effect of LINC00470 and phosphatase and tensin homolog (PTEN) on EC cell migration, invasion, tube formation in vitro, and angiogenesis in mice xenografted with tumor after gain- or loss-of-function treatments. RNA pull-down, Co-IP, and ChIP experiments were performed to analyze the targeting relationships among LINC00470, MYC and DNMT3a. Results: LINC00470 was aberrantly upregulated in EC and its high expression correlated to prognosis of EC patients. LINC00470 promoted invasiveness, migration, and angiogenesis of EC cells, and facilitated tumorigenesis and metastasis in vivo, but those effects were reversed by up-regulating PTEN. Functionally, LINC00470 bound to MYC in EC and that LINC00470 stimulated the binding of MYC to DNMT3a, and thus recruited DNMT3a through MYC to promote PTEN methylation. Conclusions: Our findings revealed that LINC00470 stimulated PTEN methylation to inhibit its expression by MYC-induced recruitment of DNMT3a, thus aggravating EC.